An Analysis On Youth Drug Abuse: Protective And Risk Factors In High-risk Area - Amin Al Haadi Shafie; Dini Farhana Baharudin; Khatijah Othman; Nurhafizah Mohamad Yasin; Salleh Amat; Rafidah Aga Mohd Jaladin; Mohd Khairul Anuar Rahimi; Ahmad Najaa' Mokhtar; Suzaily Wahab; Nurul Hanna Khairul Anuwar (UPM Press, 2024)
Indexed by WOS/Scopus/ERA/MyCite